2010
DOI: 10.1093/ndt/gfq338
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of first and second kidney transplants from the same deceased donor

Abstract: We found no difference between the successively transplanted kidneys of the same donor, not even for the expanded criteria donor organs. Nevertheless, assuming a 'safe' CIT is not justified, and CIT should always be kept as short as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
6
13
0
Order By: Relevance
“…In agreement with Giessing et al, we did not find a negative impact of prolonged cold ischemia time in successively transplanted kidneys from the same donor [18]. On the other hand, results from the largest ESP study published so far indicate that each hour of prolonged cold ischemia increases the probability of graft loss by 3% [6].…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with Giessing et al, we did not find a negative impact of prolonged cold ischemia time in successively transplanted kidneys from the same donor [18]. On the other hand, results from the largest ESP study published so far indicate that each hour of prolonged cold ischemia increases the probability of graft loss by 3% [6].…”
Section: Discussionsupporting
confidence: 93%
“…Acute rejection was not associated with CIT in our study. These findings are in accordance with the findings of some studies (9,12), but not in others (11,14). Giblin et al (14) found acute rejection rates to be significantly lower for first kidneys compared to second kidneys transplanted ( (27) reported that DGF solely due to ischemia (in the absence of rejection) correlates strongly with the presence of fibrosis in the renal allograft at 3 months posttransplant.…”
Section: Discussionsupporting
confidence: 86%
“…[10] reported similar values: donor age of 51 years and a DGF rate of 31%. In a previous study from our institution, the incidence of DGF among deceased donor renal transplant recipients reached 40% with a median donor age of 58.5 years [11].…”
Section: Discussionmentioning
confidence: 76%